External quality assessment schemes raise standards: evidence from the UKNEQAS parasitology subschemes. Issue 12 (25th November 2003) - Kettelhut, M M; Chiodini, P L; Edwards, H; Moody, A
Abstract : Background: The burden of parasitic disease imported into the temperate zone is increasing, and in the tropics remains very high. Thus, high quality diagnostic parasitology services are needed, but to implement clinical governance a measure of quality of service is required. Aim: To examine performance in the United Kingdom National External Quality Assessment Scheme for Parasitology for evidence of improved standards in parasite diagnosis in clinical specimens. Methods: Analysis of performance was made for the period 1986 to 2001, to look for trends in performance scores. Results: An overall rise in performance in faecal and blood parasitology schemes was found from 1986 to 2001. This was seen particularly in the identification of ova, cysts, and larvae in the faecal scheme, the detection of Plasmodium ovale and Plasmodium vivax in the blood scheme, and also in the correct identification of non-malarial blood parasites. Despite this improvement, there are still problems. In the faecal scheme, participants still experience difficulty in recognising small protozoan cysts, differentiating vegetable matter from cysts, and detecting ova and cysts when more than one species is present. In the blood scheme, participants have problems in identifying mixed malarial infections, distinguishing between P ovale and P vivax, and estimating the percentage parasitaemia. The reasons underlying these problems have been identified via the educational part of the scheme, and have been dealt with by distributing teaching sheets and undertaking practical sessions. Conclusions: UK NEQAS for Parasitology has helped to raise the standard of diagnostic parasitology in the UK.